BlueBerry Isolate, Pterostilbene, Functions as a Potential Anticancer Stem Cell Agent in Suppressing Irradiation-Mediated Enrichment of Hepatoma Stem Cells. (26th June 2013) - Lee, Chi-Ming; Su, Yen-Hao; Huynh, Thanh-Tuan; Lee, Wei-Hwa; Chiou, Jeng-Fong; Lin, Yen-Kuang; Hsiao, Michael; Wu, Chih-Hsiung; Lin, Yuh-Feng; Wu, Alexander T. H.; Yeh, Chi-Tai
Abstract : For many malignancies, radiation therapy remains the second option only to surgery in terms of its curative potential. However, radiation-induced tumor cell death is limited by a number of factors, including the adverse response of the tumor microenvironment to the treatment and either intrinsic or acquired mechanisms of evasive resistance, and the existence of cancer stem cells (CSCs). In this study, we demonstrated that using different doses of irradiation led to the enrichment of CD133 + Mahlavu cells using flow cytometric method. Subsequently, CD133 + Mahlavu cells enriched by irradiation were characterized for their stemness gene expression, self-renewal, migration/invasion abilities, and radiation resistance. Having established irradiation-enriched CD133 + Mahlavu cells with CSC properties, we evaluated a phytochemical, pterostilbene (PT), found abundantly in blueberries, against irradiation-enriched CSCs. It was shown that PT treatment dose-dependently reduced the enrichment of CD133 + Mahlavu cells upon irradiation; PT treatment also prevented tumor sphere formation, reduced stemness gene expression, and suppressed invasion and migration abilities as well as increasing apoptosis of CD133 + Mahlavu CSCs. Based on our experimental data, pterostilbene could be used to prevent the enrichment of CD133 + hepatoma CSCs and should be considered for future clinical testing as a combined agent for HCC patients.